Spectra belonging to XRF instrument report. Identification of ink components through XRF analysis of Azzolino documents. - Marei Hacke (Swedish National Heritage Board, 2023)
Accumulated spectra. Details given in supporting information

S2 File. XRF instrument report.

Identification of ink components through XRF analysis of Azzolino documents.

https://doi.org/10.1371/journal.pone.0283539.s002

(DOCX)

Belonging to publication

Lagerqvist Alidoost A, Hacke M, Winther T, Sandström T (2023) A closer look at the Azzolino collection. PLOS ONE 18(4): e0283539. https://doi.org/10.1371/journal.pone.0283539
Keywords: XRF; X-ray fluorescence; ink; iron-gall; 17th century; Azzolino; Queen Christina; History and Archaeology; Historia och arkeologi